Monetary policy in the ERM: Internal targets or external constraints? - Sinimaaria Ranki (Bank of Finland, 1997)
This study is concerned with the determinants of monetary policy in the ERM countries.We derive a monetary policy rule, an interest rate rule, from a minimization problem faced by the central bank. The loss fuction trades off costs of interest rate instability against benefits from successful demand management and stable exchange rate in the ERM.ERM-related considerations, particularly exogenous effects from German interest rates as well as deviations from the ERM central rates, are introduced into the analysis through the latter channel.In the empirical section of the paper, we seek to quantify the significance of the effects of the various factors on the domestic interest rate of the ERM-countries by performing regression analysis with the domestic short-term interest rate as the dependent variable.The evidence suggests that the countries can be divided into two groups.In the first group (Belgium, Denmark, France and the Netherlands) the exchange rate has deviated more from the central rate since the widening of the fluctuation bands than it did earlier.At the same time, the direct influence of German monetary policy has diminished, while the significance of the lags of the domestic interest rate has remained high or even increased.In the second group (Great Britain, Italy and Spain) the trade-off in monetary policy has been more a consideration of the two domestic factors than domestic and foreign components of the loss function.These results seem to be consistent with the interpretation that the EMS has become more symmetric, especially as regards the "core" countries.One could also interpret the development of the role of the EMS as a gradual introduction of an implicit coordination mechanism through which countries have sought to improve interest rate convergence by coordinating their policy targets.In this way, the role of the ERM as a constraint on achieving policy targets has decreased.
URN:NBN:fi:bof-20140807472
Keywords: 330; ERM; reaction function; exchange rates; monetary policy